2001
DOI: 10.1152/ajpgi.2001.281.4.g931
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and gastrointestinal expression of rat hephaestin: relationship to other iron transport proteins

Abstract: The membrane-bound ceruloplasmin homolog hephaestin plays a critical role in intestinal iron absorption. The aims of this study were to clone the rat hephaestin gene and to examine its expression in the gastrointestinal tract in relation to other genes encoding iron transport proteins. The rat hephaestin gene was isolated from intestinal mRNA and was found to encode a protein 96% identical to mouse hephaestin. Analysis by ribonuclease protection assay and Western blotting showed that hephaestin was expressed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
96
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 123 publications
(101 citation statements)
references
References 34 publications
3
96
1
Order By: Relevance
“…The cytoplasmic Fe(II) can efflux from the enterocyte at the basolateral surface via the Fe(II) permease Fpn. As noted above, this efflux is dependent on the ferroxidation due to Hp (27,29,54,61,73,74); in plasma, the product of this coupled permeation-oxidation is likely ferric Tf. The redox cycling in Ft (Fig.…”
Section: Ferrireductases and Ferroxidases Are The Iron Metabolic Pathwaymentioning
confidence: 91%
“…The cytoplasmic Fe(II) can efflux from the enterocyte at the basolateral surface via the Fe(II) permease Fpn. As noted above, this efflux is dependent on the ferroxidation due to Hp (27,29,54,61,73,74); in plasma, the product of this coupled permeation-oxidation is likely ferric Tf. The redox cycling in Ft (Fig.…”
Section: Ferrireductases and Ferroxidases Are The Iron Metabolic Pathwaymentioning
confidence: 91%
“…Immunolocalization experiments in IEC-6 cells isolated from the small intestine have identified hephaestin in the perinuclear region of the cells. Although this protein has also been detected on the plasma membrane, the labeling was weak and the exact region of membrane to which it is localized was not determined (Frazer et al, 2001;Simovich et al, 2002). It has been suggested that this protein may mediate the intracellular transport of Fe, and possibly Cd 2+ , to MTP1.…”
Section: Mimicry and Intestinal Transport Of CD 2+mentioning
confidence: 99%
“…The iron can then be either stored in an inert form bound to ferritin (22), used by the cell, or exported from the enterocyte via a pathway that requires the ferroxidase hephaestin (23,24) and the basolateral iron transporter ferroportin (25). Iron is transported in the serum bound to transferrin, which interacts with transferrin receptor 1 (TfR1) on the plasma membrane of cells that take up iron.…”
mentioning
confidence: 99%